Analisis Teori Daniel Goleman dalam Perkembangan Kecerdasan Emosi Anak Usia Dini - Chintya, Risma; Sit, Masganti (Absorbent Mind, 2024)
Early childhood is an important phase in a person's development. In this period, children are experiencing rapid growth and development, both physically, mentally, and emotionally. This period is also an important foundation in shaping a child's personality, skills, and mindset in the future. The aim of this research is to analyze the development of emotional intelligence in early childhood to collect data that will be used for various purposes from observing the development of emotional intelligence in early childhood according to gelomen theory. This research method is through a literature approach or literature study, which is a study used through searching for journal articles, books about emotional development in early childhood and according to experts' opinions regarding emotional development. The results of this research reveal that emotional intelligence includes the ability to recognize, understand, manage, and direct one's own and other people's emotions. There are four main components in emotional intelligence, namely self-awareness, self-management, social awareness, and relationship management. Emotional intelligence also includes a person's ability to regulate emotions, maintain and choose ways of expressing them through self-awareness, self-control, empathy, motivation, and social skills.